Efeito da remoção parcial de cárie no comportamento biomecânico de restaurações classe II com compósito “bulk-fill” - Silva, Paula Fernanda Damasceno (2018)
In deep caries lesions, the maintenance of caries-affected dentin (partial caries removal) under the final restoration has been recommended to avoid additional damage to the pulp, but the effects of the presence of this more resilient dentin tissue under restoration is not yet fully elucidated. Thus, this study aimed to develop a method to induce caries in the dentin using acid challenge associated to a microcosm biofilm model, and to determine the effect of maintaining caries-affected dentin under composite restoration in its biomechanical behavior. Twenty third molars, with class I cavity preparation, were exposed to acetic acid demineralizing solution for 32 days. Afterwards, microcosm biofilm was cultured for 7 days on the demineralized dentin, under daily 6 hours regimen of sucrose. The caries-affected dentin was removed in half of the samples, while it was maintained in the others (n = 10). The proximal walls were also removed and the class II cavities restored with the composite Filtek Bulk-Fill. The deformation of the buccal and lingual cusps was evaluated by strain gauges during the restorative procedure. The presence of cracks in these cusps was also analyzed by transillumination before and after the restorative procedures. Four samples (n = 2) were used to volumetrically measure cusp deformation by differences in the images obtained before and after the restoration with micro computed tomography. Afterwards, all samples were submitted to 1,200,000 mechanical cycles and the crack propagation was analyzed; followed by fracture resistance test. Data of cusp strain and averages of crack/ tooth were submitted to two-way repeated measures ANOVA. Fisher's exact test was used to evaluate the effect of caries removal on the proportion of cracks larger and shorter than 3 mm. Data of the fracture strength were submitted to the T-test. The level of significance was set at 5% for all analyzes. Caries removal did not affect the presence and distribution of cracks, cusp deformation, and fracture strength of teeth restored with composite. The restorative procedure increased the number of cracks, which was not affected by mechanical cycling. As conclusion, maintaining caries-affected dentin under composite restorations did not affect their biomechanical behavior.